Six mutagenicity assays in exposure biomonitoring of patients receiving carbamazepine for epilepsy or trigeminal neuralgia - Sinués, B.; Gazulla, J.; Bernal, M.L.; Lanuza, J.; Fanlo, A.; Saenz, M.A.; Bartolome, M. (Mutation Research, 1995)
The mutagenic potential of carbamazepine (CBZ) therapy has been studied in 37 patients undergoing long-term treatment with this drug. Of the total group, 23 patients suffered from epilepsy and 14 from trigeminal neuralgia. Thirty-one healty subjects served as controls. Six mutagenicity assays with different end-points were performed. The possible cytogenetic alterations were evaluated by analyzing sister-chromatid exchange frequencies (SCE), chromosome aberrations (CA), micronuclei (MN), proliferation indices (PRI), and mitotic indices. The Salmonella assay with and without microsomal activation served to measure urinary mutagenicity. The results show that CBZ leads to an increase in SCE ( p < 0.01) and PRI ( p < 0.05) but had no effect on the other cytogenetic parameters. CBZ was negative in the urine mutagenicity test. Plasma levels of total CBZ, free CBZ and CBZ-10, 11-epoxide did not correlate with the cytogenetic alterations. Even though folic acid and γ-glutamyltranspeptidase were significantly different in patients and controls, there was no significant association between these values and SCE or PRI. Patients with epilepsy and those with trigeminal neuralgia did not differ with respect to the end-points analyzed.